1986
DOI: 10.1007/bf00614310
|View full text |Cite
|
Sign up to set email alerts
|

Renal excretion and pharmacokinetics of methotrexate and 7-hydroxy-methotrexate following a 24-h high dose infusion of methotrexate in children

Abstract: In children with lymphoid malignancies 18 courses of methotrexate (18-200 mg/kg) administered as a 24-h infusion were monitored. Plasma concentrations and renal excretion rates of methotrexate (MTX) and 7-hydroxymethotrexate (7-OHMTX) were determined. A low correlation was found between the administered dose of MTX and the body exposure to MTX or 7-OHMTX. Although 84% of the MTX eventually recovered from the urine was excreted during the 24 h of the infusion, the renal clearance of MTX was markedly lower durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In conclusion, even though we have shown that, in-vitro, liver aldehyde oxidase from man catalyses the oxidation of methotrexate to 7-hydroxymethotrexate, turnover is low. During high-dose therapy 33% of the parent drug is (Ertmann et al 1985;Winograd et al 1986). Despite this, aldehyde oxidase is responsible for some of this conversion; perhaps the closely related xanthine oxidase is also responsible for the formation of 7-hydroxymethotrexate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, even though we have shown that, in-vitro, liver aldehyde oxidase from man catalyses the oxidation of methotrexate to 7-hydroxymethotrexate, turnover is low. During high-dose therapy 33% of the parent drug is (Ertmann et al 1985;Winograd et al 1986). Despite this, aldehyde oxidase is responsible for some of this conversion; perhaps the closely related xanthine oxidase is also responsible for the formation of 7-hydroxymethotrexate.…”
Section: Resultsmentioning
confidence: 99%
“…After high-dose therapy with the folate antagonist, methotrexate (10-methyl-4-pteroyl-L-glutamic acid), serum levels of its major metabolite, 7-hydroxymethotrexate, can be up to 100 times those of the parent drug, and up to 33% of the dose is excreted as 7-hydroxymethotrexate (Ertmann et al 1985;Winograd et al 1986). However, the metabolic origins of 7-hydroxymethotrexate, at least in man, are unclear.…”
mentioning
confidence: 99%
“…Inthe caseof7-OHMTX, itwasassumed that10%ofthe MTX dosewastransformedintothe metabolite. Asimilarapproachwasu sed in apopulation studyw ithadult cancerpatients [22].Itiss upported bymeasurements of the cumulativeexcretiono fMTX and 7-OHMTXin adults withsolid cancers [23], in children withl ymphoid malignancies [12]a s well asbyour measurementof the cumulativerecovery of the dosei nurine collected upto1 20 hi ntwop atients (65% and 55 %asMTX, and 8% and 9% as7 -OH MTX, respectively). Totalclearanceatt he steady-statewascalculated asfollows: CL =R/c ss whereRisthe rateofthe infusion and c ss isthe steady-statep lasmac oncentration.…”
Section: Pharmacokinetica Nd Statisticalanalysesmentioning
confidence: 99%
“…Population pharmacokinetica nalysishas notbeen performed yetin children withALL and older studiesdo notr eport the kineticsof 7-OHMTX in sufficientdetail. Furthermore,onlyfewstudiesexamined the renalexcretion of MTX and 7-OH MTX in children treated withHDMTX [12].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 One patient receiving low-dose dopamine 2-3 mg/kg bw/min infusion. Dopamine at ''renal'' dosage is a known glomerular vasodilator, that reduce resistances and improves renal blood flow.…”
Section: Letter To the Editormentioning
confidence: 99%